Positive and negative emotional arousal increases duration of memory traces: common and independent mechanisms - Cruciani, Fabio; Berardi, Andrea; Cabib, Simona; Conversi, David (Frontiers in Behavioral Neuroscience, 2011)
We compared the ability of positive and negative emotional arousal to increase the duration of consolidated memory traces. Positive arousal was modulated by manipulating the motivational salience of the testing cage of an object recognition test (ORT). Negative emotional arousal was modulated by manipulating shock levels in a step-through inhibitory avoidance (IA). Mice trained in either a high (chocolate-associated) or a low (inedible object-associated) emotionally arousing cage showed discrimination of a novel object 24 hours after training, but only mice trained in the more arousing cage showed retention 96 hours after training. Mice trained with either low (0.35 mA) or high (0.7 mA) shock intensities showed increased step-through latencies when tested 24 hours after training, but only mice trained with the higher shock intensity showed retention of the inhibitory avoidance learning 1 week after training. Administration of the phosphodiesterase type IV inhibitor Rolipram immediately after training in the two low arousing conditions increases duration of both responses.